Management of Education Quality Assurance at Roudlotun Nasyiin High School in Mojokerto - Amrozi Khamidi; Syunu Trihantoyo; Muhamad Sholeh; Mufarrihul Hazin (Tamilis Synex: Multidimensional Collaboration, 2024)
Implementation of the education quality assurance system at the secondary level is needed to create a good quality culture and improve the achievement of guaranteed fulfillment of standards in educational units. The achievement of quality assurance is based on the principles, objectives, indicators, strategies and factors that affect the quality itself. By using the principal interview technique, researchers conducted research to find out the existing school quality assurance system at Roudlotun Nasyiin High School in Mojokerto such as (1) the scope of quality assurance, (2) quality assurance stages, (3) influencing factors, (4) obstacles and efforts to implement the quality assurance system. The implementation of the education quality assurance system at Roudlotun Nasyiin High School in Mojokerto has been categorized as good because its implementation is adjusted to existing educational procedures and standardization. The stages of implementing the quality assurance system include planning, implementation, evaluation, assessment, corrective action and development. Factors that can affect the achievement of quality include: curriculum, learning media, human resources, and learning systems. The obstacles in quality management at Roudlotun Nasyiin High School in Mojokerto are the lack of appreciation of the school community for the quality and productivity of quality management. Schools improve school quality and make changes in the application of quality management principles in learning.